2010
DOI: 10.1590/s1982-21702010000400003
|View full text |Cite
|
Sign up to set email alerts
|

Avaliação do potencial da interferometria sar para o mapeamento altimétrico de áreas reflorestadas por eucalyptus sp

Abstract: RESUMOEste trabalho tem como objetivo avaliar a qualidade altimétrica dos modelos de elevação (MDE) gerados através da interferometria SAR (Synthetic Aperture Radar) nas bandas X e P, em diferentes polarizações em áreas florestadas. Este estudo foi realizado no município de Pindamonhangaba/SP, em uma área caracterizada por reflorestamento de Eucalyptus saligna de 6 anos de idade, cujo inventario florestal e levantamento topográfico foram realizados no mesmo período do aerolevantamento. Verificou-se que nesta á… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 3 publications
(3 reference statements)
1
2
0
Order By: Relevance
“…The process of feature selection was unanimous in selecting the interferometric height (Hint) as the most relevant feature for all areas of study, both in the case of qualitative and quantitative theme-features, in agreement with the results obtained by [23][24][56][57]. Likewise, there was an emphasis on features obtained by target decomposition techniques on the L band, from the ALOS PALSAR 2 sensor.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…The process of feature selection was unanimous in selecting the interferometric height (Hint) as the most relevant feature for all areas of study, both in the case of qualitative and quantitative theme-features, in agreement with the results obtained by [23][24][56][57]. Likewise, there was an emphasis on features obtained by target decomposition techniques on the L band, from the ALOS PALSAR 2 sensor.…”
Section: Discussionsupporting
confidence: 76%
“…By 2022, a total area of 1,800,000 km 2 of the Amazon region will be covered with airborne sensors in the X and P bands [21]. In addition to the 1:50,000 scale mapping, the project also has the potential to generate data to support infrastructure projects and sustainable exploitation of natural resources in the region [22][23][24].…”
mentioning
confidence: 99%
“…The authors observed good prediction of tree diameter, commercial height and volume data, with determination indices ranging from 84 to 88% against forest inventory in field, indicating, therefore, the high potential of SAR interferometry to be used as support in inventories of large areas. Gama et al (2010a) using SAR interferometry in X and P bands, with different polarizations to generate elevation models (EM) and assess altimetric quality estimate in populations of Eucalyptus, observed that, in forest area, P band and particularly HH polarization suffer lower disturbance for interacting with the vegetation horizontal components instead of vertical components. Gama et al (2010b) by integrating polarimetry and interferometry modeled volume and biomass of Eucalyptus planted forests, observed a prediction error of around 10% for both variables using the models with combination of interferometric height and Canopy Scattering Index (CSI) which is obtained by the relation of backscatter coefficient (σ°) VV by the sum of σ°V V and σ°H H , using X and P band SAR and OrbiSAR-1 (airborne radar) sensor images.…”
Section: Radar Applications and Forest Biophysical Data In Brazilmentioning
confidence: 99%